IN SILICO AND IN VITRO ANALYSIS OF BLASHV AND BLATEM GENE PRIMERS - Khoiro, Aisha Azaria Nisa’ul; Purwanti, Elly; Miharja, Fuad Jaya; Ariesaka, Kiky Martha; Nuryady, Moh. Mirza (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
Bacterial pollution that occurs in the environment causes an increase in disease and antibiotic use, which leads to resistance. This study analyzes antibiotic-resistant blaSHV and blaTEM genes in silico and in vitro. Antibiotic-resistant bacterial isolates on ESBL will be carried out PCR and electrophoresis. The type of research used is descriptive observational research conducted from April to September 2024. The sampling technique used was random sampling. Primer blaSHV with sequence F' AGGATTGACTGCCTTTTTG and R' ATTTGCTGATTTCGCTCG, while primer blaTEM has sequence F' ATCAGCAATAAACCAGC and R' CCCCGAAGAACGTTTTC. Data analysis was carried out by analyzing in silico results obtained from the NCBI website and observing the visualization results of PCR amplification indicated by the presence of DNA bands.  In silico results showed 25 organisms attached to blaSHV and 29 organisms to blaTEM. In vitro results shown by electrophoresis visualization showed blaSHV amplicons measuring 392 bp with an annealing temperature of 50.5°C, and blaTEM measuring 517 bp with an annealing temperature of 42°C. The success rate of PCR was shown by clear and specific amplification of both genes, indicating that the PCR method performed was effective in detecting blaSHV and blaTEM genes in ESBL antibiotic-resistant bacterial isolate samples.